2019
DOI: 10.1016/j.cell.2019.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Neural Activity and Encoding of Behavior across Brains of Socially Interacting Animals

Abstract: Highlights d Simultaneous imaging of interacting mice reveals interbrain synchrony of activity d Interbrain synchrony arises from ongoing social interaction between animals d Synchrony emerges from neurons encoding behavior of oneself and the social partner d Interbrain synchrony predicts future social decisions and dominance relationships

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
228
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(265 citation statements)
references
References 48 publications
19
228
3
2
Order By: Relevance
“…Multiple lines of evidence indicate that the IL-PFC processes social information and modulates fear responses, although few studies have examined the potential convergence of these functions. The IL-PFC exhibits robust neuronal activity during social interaction [31][32][33], and we confirmed that interaction with either a novel or familiar conspecific results in increased c-fos + expression within this region [52]. Likewise, the IL-PFC is required for extinction of fear [44,53,54].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Multiple lines of evidence indicate that the IL-PFC processes social information and modulates fear responses, although few studies have examined the potential convergence of these functions. The IL-PFC exhibits robust neuronal activity during social interaction [31][32][33], and we confirmed that interaction with either a novel or familiar conspecific results in increased c-fos + expression within this region [52]. Likewise, the IL-PFC is required for extinction of fear [44,53,54].…”
Section: Discussionsupporting
confidence: 76%
“…Given the highly conserved nature of social buffering, its underlying neural mechanisms are hypothesized to be shared across taxa [12,30]. In particular, the PFC modulates social behavior [31][32][33], fear responses [34,35], and resilience to stressors [36][37][38]. Critically, inhibition of the PFC with the GABA agonist, muscimol, blocks the effects of social familiarity in reducing anxiety-like behaviors (Lungwitz et al, 2014), suggesting a potentially direct role for the PFC in social buffering of fear and/or anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, imaging approaches can reveal how individual cells embedded in a larger network display coordinated activity during different stages of behavior or training (Wagner et al 2017;Heffley et al 2018;Galiñanes, Bonardi, and Huber 2018;Giovannucci et al 2017) . Moreover, because of their ability to record in freely moving animals, miniscopes have been instrumental in uncovering neural activity patterns occurring during natural behaviors and related brain-states including social interactions (Murugan et al 2017;Remedios et al 2017;Liang et al 2018;Kingsbury et al 2019) or sleep Cox, Pinto, and Dan 2016) with fully intact vestibular input.…”
Section: Introductionmentioning
confidence: 99%
“…RM is an unconscious, congruent, and rapid response (less than 1 s) during which human and non-human animals automatically mimic others' expressions and movements [13,32]. RM has been demonstrated not only in humans but also in several primate [33][34][35][36], rodent [27,37], and carnivore species [31,38,39].…”
Section: Rapid Mimicry: the Key For Fair Play And Bonding Successmentioning
confidence: 99%